An Investigation of University Studentsâ€™ Awareness on Cyber Security - Khalid, Fariza; Yusoff Daud, Md; Jasmy Abdul Rahman, Mohd; Khalid Mohamad Nasir, Md (International Journal of Engineering and Technology, 2018)
The emergence of various online applications and abundance of exposure to the use of social media nowadays had put users in higher potential to online related risks. Racial abuse, cyber-bullying, online fraud, addiction towards gaming and gambling and pornography are among the risks that online users may be exposed to in their daily life. To protect oneself from these risks, it has to come from self-awareness. This research aims to investigate university students' awareness of cybersecurity. Research data was collected using a set of questionnaire to 142 second-year students in the faculty of education in one of the universities in Malaysia. Descriptive data analysis was done using an SPSS software. The result of this study showed that even though these university students demonstrated a high level of awareness on certain elements in cyber security such as cyber bully, personal information, and internet banking, there are still lacking appropriate knowledge on the aspect of cyber-sex and self-protection. This paper also discusses the role of all level of community in educating children and young adults in this matter.Â Â